Private Companies in Europe: The societas unius personae (SUP) and the recent developments in the EU Member States - Vera González, Jorge (Cizur Menor, Navarra Aranzadi, 2016)
This book contains the second contribution of the ""Forum for the study of the closely held companies in Europe”. In the first part, the study group analyses thoroughly the Proposal for a Directive of the European Parliament and of the Council on single-member private limited liability companies (Societas Unius Personae - SUP). In the second part the research group dwell on specific important problems of the closely held companies in the different EU Member States.
Keywords: Derecho comunitario